Association of lipid levels with motor and cognitive function and decline in advanced Parkinson's disease in the Mark-PD study. (April 2021) - Choe, Chi-un; Petersen, Elina; Lezius, Susanne; Cheng, Bastian; Schulz, Robert; Buhmann, Carsten; Pötter-Nerger, Monika; Daum, Günter; Blankenberg, Stefan; Gerloff, Christian; Schwedhelm, Edzard; Zeller, Tanja
Abstract: Objectives: In prospective cohort studies different blood lipid fractions have been identified as risk factors of Parkinson's disease (PD). However, data relating lipoproteins to disease phenotypes and progression in advanced PD patients are sparse. Therefore, we assessed the most common lipoproteins in a case-control design and evaluated their associations with motor and cognitive function and decline in PD patients. Methods: Triglycerides, LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C), apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), and lipoprotein a (Lp(a)) were analyzed in 294 PD patients of the MARK-PD study cohort and 588 controls matched for age, sex and cardiovascular risk factors. In PD patients, motor (MDS-UPDRS III, Hoehn-Yahr stage) and cognitive function (MoCA) were examined. In a sub-cohort (n = 98 patients), baseline lipid levels were correlated with motor and cognitive disease progression during a follow-up period of 523 ± 199 days. Results: At baseline, HDL-C levels were lower in PD patients compared to matched controls after adjustment. We observed a very weak association of Lp(a) levels with UDPRS III scores. In cross-sectional analyses, no other lipid fraction revealed a significant and consistent association with motor or cognitive function. During follow-up, no lipid fraction level was associated with motor or cognitive progression. Conclusion: In advanced PD, there is no strong and consistent association of lipid levels with motor or cognitive function and decline. Highlights: HDL-C levels are lower in PD patients compared with matched controls. No lipid level strongly and consistently associates with motor or cognitive function. No lipid level predicts motor or cognitive decline in advanced PD patients.